Multivariate analysis of Bivalvia population in the Cunda Strait mangrove ecosystem, Lhokseumawe, Indonesia - Syahrial, Syahrial; Ruzanna, Arina; Anggraini, Rika; Habib EY, M.; Ikhsan, Nur; Pane, Andina Ramadhani Putri; Khalil, Munawar (Journal of Marine Studies, 2025)
Research on the diversity and density of Bivalvia populations as indicators of coastal ecosystem health, particularly using multivariate statistical approaches, remains limited in Lhokseumawe, Indonesia. This study aims to analyse the distribution and abundance of Bivalvia in the Cunda Strait mangrove ecosystem using multivariate statistical techniques. Field sampling was conducted in May 2024 at five observation stations, where Bivalvia were collected using a 1 x 1 m transect method. Data analysis included cluster analysis, non-metric multidimensional scaling (nMDS), analysis of similarity (ANOSIM), and similarity percentage analysis (SIMPER) to assess species diversity and population density. A total of 10 Bivalvia species, representing five genera and four families, were identified. The Shannon-Wiener diversity index ranged from 0.99 to 1.53, classifying the Bivalvia community into four distinct groups. Population density analysis revealed that Anadara sp2, Donax sp2, and Anadara sp1 exhibited the highest densities (4.80 ind/m², 2.80 ind/m², and 2.00 ind/m², respectively). Cluster and nMDS analyses further divided the Bivalvia density in the Cunda Strait into two distinct groups. The Bray-Curtis similarity index, applied by ANOSIM, indicated significant variation in the density of the Bivalvia population between observation stations (p < 0.05). SIMPER analysis identified Polymesoda sp as a key distinguishing species between multiple station pairs, including Stations 1 and 2, 1 and 3, 1 and 4, 1 and 5, 2 and 5, 3 and 5, and 4 and 5. Furthermore, Anadara sp2 was the main differentiating species between Stations 2 and 3, as well as between 2 and 4, while Anadara sp1 distinguished Stations 3 and 4. These findings highlight the spatial heterogeneity of Bivalvia communities in the Cunda Strait and underscore the utility of multivariate statistical approaches in coastal biodiversity assessments.